IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA INDONESIA PADA SMA NEGERI 8 BULUKUMBA - Wulandari, Andi Novianti; Munirah, Munirah; Yusuf, Akram Budiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Implementation of the Independent Curriculum in Indonesian Language Learning at SMA Negeri 8 Bulukumba. The objectives to be achieved in this research are (1) Knowing the Implementation of the Independent Curriculum in Indonesian Language Learning at SMA Negeri 8 Bulukumba. (2) Knowing the Project for Strengthening the Profile of Pancasila in the Indonesian Language Learning Process at SMA Negeri 8 Bulukumba. Using descriptive qualitative research methods by applying case study research, while technical data collection is observation, interviews, and documentation, and data analysis techniques use the Miles, Huberman, and Saldana model which includes data collection, data condensation, data presentation and conclusions. . The results of this research are (1) the implementation of Indonesian language learning in the independent curriculum at SMA Negeri 8 Bulukumba has been carried out well. The Indonesian language teachers at SMA Negeri 8 Bulukumba have carried out careful planning, implemented active and creative teaching, used relevant and differential learning materials. (2) Carrying out training preparations for the Strengthening Pancasila Student Profile Project (P5) in the initial stage, namely implementing the coordinator from deputy principals who have experience in developing and managing projects, managing the systems needed by a team of educators and students in order to complete the project successfully, ensuring teaching collaboration occurs between educators who are members of the profile project facilitator team, and paying attention to the needs and each student's interest in learning so that they can provide various challenges, according to learning style, imagination, creation and innovation, as well as interest in sports week projects, art performances and local poetry creation with the theme Bhinneka Tunggal Ika can bring out six dimensions of the Pancasila student profile at once.